Basil essential oil-incorporated bacterial nanocellulose foam: Fabrication, characterization, and application in extending ground beef shelf life - Anita Lotfi Javid; Hadi Almasi; Rahim Molaei; Mehran Moradi (Journal of Agriculture and Food Research)
Bacterial nanocellulose (BNC) is a sustainable antimicrobial material for food packaging. To enhance its antimicrobial properties, basil (Ocimum basilicum L.) essential oil (BEO) was incorporated into the BNC porous foam. A spray method was used with low BEO concentrations (1 and 2 μL/cm2) based on foam surface to optimize BEO usage while maintaining its antimicrobial effectiveness. BNC was synthesized using Komagataeibacter xylinus. The minimum inhibitory concentrations were 128 and 64 μg/mL for Pseudomonas aeruginosa and Listeria monocytogenes, respectively, demonstrating greater sensitivity of Gram-positive bacteria compared to Gram-negative bacteria. The use of BEO in spray form increased the antimicrobial and antioxidant activities (as measured by DPPH and ABTS methods) of foams. The absorption bands related to BEO in Fourier transform infrared spectroscopy analysis of the BNC-BEO foam confirmed the incorporation of BEO into the BNC foam. Impregnation with BEO at 1 and 2 μL/cm2 significantly increased the water contact angle to 31.62° and 33.19°, respectively, thereby enhancing the hydrophobicity of the foam, but reduced the mechanical strength of the BNC-BEO foams. Foams were used in active packaging of ground beef to improve shelf life by controlling microbial and oxidative processes. The BNC-BEO foam showed a slower microbial growth rate, with bacterial populations about 1–2 log₁₀ CFU/g lower than control. Meat samples packaged with BNC-BEO foams scored higher in terms of taste and odor. A significantly lower amount of BEO was used in the foam form of BNC, which is favorable for improving sensory parameters. Therefore, BNC-BEO can be applied to the active packaging of meat.